752 views
1 vote
Simplify this expression ( 2-5 square root 6) x 3 square root of 2

2 Answers

6 votes

6Г2-30Г3 D

Explanation:

User Basuro
by
5.7k points
4 votes

Answer:
6√(2)-30√(3)

Explanation:

Remember that:


(√(a))(√(b))=√(ab)


\sqrt[n]{a^n}=a

Given the following expression:


(2-5√(6))(3√(2))

The steps to simplify this expression, are:

1. Apply the Distributive property:


=(2)(3√(2))-(5√(6))(3√(2))=6√(2)-15√(12)

2.Since:


12=2*2*3=2^2*3

You can rewrite the radicand 12 in this form:


=6√(2)-15√(2^2*3)

3. Simplifying, you get:


=6√(2)-(15)(2)√(3)=6√(2)-30√(3)

4. Notice that the indices of the Radicals are the same, but the radicands don't, then, you can subtract the Radicals.

User LogicLooking
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.